STATE SUPPORT AGRARIAN SECTOR IN MODERN TERMS OF MENAGEMENT - Levandivskyi, O.T. (The actual problems of regional economy development, 2018)
Approaches to study of state support of agrarian a sector in the modern term are investigated in the article. Basic approaches are pointed in genesis of this problem. It is marked that modern conduct of agriculture are closely related to state support. Separate directions of state supporting are grounded. It is considered that state supporting of agrarian a sector is the important instrument of steady development of the state and providing of it food safety. However in the modern terms question of organization of the financial providing agrarian the sector of economy needs new approach, improving of the considered programs of state support by means of conducting of active measures at the level of agroenterpreneurs, introduction of new investment structures. It is marked that organizating and conducting of agricultural production, and also developing of measures of improving of its organizational and economic mechanism it is necessary to take into account the features of agricultural activity without which is impossible to attain the high level of efficiency of production.